Atlas and wavenumber tables for the visible part of the electronic-vibro-rotational D2 spectrum emitted by low-temperature plasma. (October 2016) - Lavrov, Boris P.; Umrikhin, Ivan S.
Abstract: The visible part (≈ 419–696 nm) of the multiline electronic-vibro-rotational (rovibronic) emission spectrum of the D2 molecule was recorded with a moderate resolution mainly determined by Doppler broadening of spectral lines (the observed line widths are equal to 0.0122(4) nm throughout the wavelength range under study). After the numerical deconvolution of the recorded intensity distributions and proper spectrometer calibrations, the new set of wavenumber values for rovibronic spectral lines has been obtained. It is shown that these new data are significantly more precise than experimental wavenumber values currently published for the visible part of the D2 spectrum, except for the fragmentary results of our high-resolution experiments (Phys. Rev. A, 2012). The assignments of the triplet rovibronic lines are verified by means of the optimizational technique based on two general principles: Rydberg–Ritz and maximum likelihood (J. Phys. B, 2008). Final results (reported in the on-line supplement material) include an atlas and accompanying tables. The atlas is divided into 158 sections (each section covers about 1.5 nm) containing images of the focal plane of the spectrometer and intensity distributions in linear and logarithmic scales. The tables contain wavenumber and relative intensity values for 11 941 spectral lines together with the available and new line assignments for the D2 and HD molecules. Abstract : Highlights: Atlas for visible part of D2 rovibronic spectrum is created for the first time. Atlas is reliable, timesaving tool for recognizing D2 lines in plasma spectroscopy. Assignments for triplet rovibronic lines are verified by optimizational analysis. New set of wavenumber values is obtained by deconvolution of recorded spectra. New wavenumber values are sufficiently more precise than those reported to date.